Effects of Landslide on the Livelihood of People at Ghumthang, Sindhupalchok - Shrestha, Mandip (Journal of APF Command and Staff College, 2022)
Landslides are considered as one of the most recurring and common disaster in Nepal. They cause huge loss to infrastructure, property and human casualty. The intensity of landslides in Nepal’s mid hills are rising as one of the most common and devastating disasters. The 2020 Ghumthang landslide in Nepal’s Sindhupalchok District destroyed the houses, lands and infrastructures and impacted livelihoods of the people living in the area. Every monsoon landslides in hilly region of the country lead to impact on the livelihood of the people and this aspect has not been analyzed in depth. The disaster-affected people face the destruction crop, livestock, and land. They also face damages of house, drinking water and other infrastructure,. In addition they face non-economic effects like health and mental stress. This article based on a household survey combines quantitative and qualitative data from 50 respondents. Questionnaire, interviews and focus group discussions were held during field survey to solicit their persctives Secondary sources were consulted and lived experience used to triangulate the survey findings for accuracy. This study reveals multidimensional nature of the impact of landslide on the life of people who live in the affected area.